LEGAL PROTECTION OF WOMEN AND CHILDREN FROM VIOLENCE IN THE PERSPECTIVE OF REGIONAL REGULATION OF BULELENG REGENCY NUMBER 5 YEAR 2019 - Ni Putu Rai Yuliartini (Universitas Pendidikan Ganesha, 2021)
In the context of preventing and overcoming violence against women and children in Buleleng Regency, it is necessary to protect women and children victims of violence in the form of Regional regulations. The protection of women and children victims of violence in the regions requires institutional support and regulations that can guarantee its implementation. Regional regulations regulate protection efforts for victims, especially in terms of prevention, service, and empowerment of women and children victims of violence in Buleleng Regency.